Radish cultivation with hydrogel doses combined with different water slides in drip irrigation system (Research, Society and Development, 2021)
Radish yield and quality are factors influenced by water stress that may occur during periods of drought or irrigation handled inappropriately, interfering negatively in plants development, producing radishes of inferior quality and in lesser quantity. In addition to irrigation, which makes water available in the system, it is important to maintain it with the use of water-retaining products such as hydrogel. The aim of this work was to evaluate radish yield, submitted to three different hydrogel doses combined with two water slides. The experimental design was in factorial scheme 3 x 2, with three water slides (50%, 75% and 100% Eto – reference evapotranspiration estimate) and two hydrogel doses (40 and 60 g m-2) with four replicates. Number of leaves, horizontal and vertical root diameter (mm), total and shoot length (cm), fresh mass of root and shoot (g), dry mass of shoot and root (g) and yield (t ha-1) were evaluated. The best results, regarding radish production and development, were obtained when using 50% of Eto with 60 g m-2 of hydrogel in combination. Thus, radish cultivation in oxisoil was influenced by the use of hydrogel, which provided a more efficient water level use.